Development of a Writing Rating Scale for Culture- and Context-Specific Educational Setting in Ukraine - Ольга Квасова; Тамара Кавицька; Вікторія Осідак; Ентоні Грін (Taras Shevchenko National University of Kyiv, 2022)
In the Ukrainian university context, the assessment of writing in language programs has traditionally been performed by the individual teacher, with no institutionally mandated scales or criteria to rely on. The use of rating scales from external proficiency tests cannot meet the requirement of total alignment with the curricula taught in context-specific settings. This is obvious in terms of frequent mismatches of course objectives and test construct as well as task types employed on the external and local tests. To address he tissue, this paper reports on efforts to introduce a rating scale for collective use by teachers across a department teaching English to students majoring in Linguistics. Although teacher raters can be trained to employ external rating scales consistently, we believe that it is both more valuable in terms of professional development and more likely to result in acceptance of the scales if they engage in scale development. The evidence we collected suggests that the collaborative approach adopted in this study can offer a sustainable template for improving the poor standards of tests and examinations in our country (and elsewhere), which often result from a lack of testing and assessment expertise among those who prepare assessment materials.